2008
DOI: 10.1186/1742-4690-5-92
|View full text |Cite
|
Sign up to set email alerts
|

Physical and in silico approaches identify DNA-PK in a Tax DNA-damage response interactome

Abstract: Background: We have initiated an effort to exhaustively map interactions between HTLV-1 Tax and host cellular proteins. The resulting Tax interactome will have significant utility toward defining new and understanding known activities of this important viral protein. In addition, the completion of a full Tax interactome will also help shed light upon the functional consequences of these myriad Tax activities. The physical mapping process involved the affinity isolation of Tax complexes followed by sequence ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…The HTLV-1 Tax protein increases cellular proliferation (55,61), inhibits apoptosis (62), impairs cell cycle checkpoints (62,63), and induces DNA damage (64)(65)(66)(67)(68). We wondered whether Tax also contributes to HTLV-1-induced autophagosome accumulation ( Fig.…”
Section: Htlv-1 Infection Induced Autophagosome Accumulationmentioning
confidence: 99%
“…The HTLV-1 Tax protein increases cellular proliferation (55,61), inhibits apoptosis (62), impairs cell cycle checkpoints (62,63), and induces DNA damage (64)(65)(66)(67)(68). We wondered whether Tax also contributes to HTLV-1-induced autophagosome accumulation ( Fig.…”
Section: Htlv-1 Infection Induced Autophagosome Accumulationmentioning
confidence: 99%
“…DNA damage induced by Tax and other oncoproteins has been documented previously (11,31,37). Earlier, it was suggested that such oncogene-induced DNA damage may have occurred indirectly through accelerated G 1 cell cycle progression, which might in itself be mutagenic (11).…”
mentioning
confidence: 99%
“…The viral oncoprotein Tax increases the rate of transcription from the viral long terminal repeat (LTR) (12,15,23). In addition, Tax can modulate the expression or activities of numerous cellular proteins involved in cell proliferation and differentiation, cell cycle regulation, and DNA repair processes (11,30,36,37,42). The pleiotropic effects of Tax on cellular processes are required for its transforming and oncogenic capabilities and play a critical role in HTLV-induced cellular transformation (16,(39)(40)(41).…”
mentioning
confidence: 99%